Analysis of Sustainable Livelihood level and its Influence on Community Vulnerability of Surumana Village, Central Sulawesi - Ardiyanto Maksimilianus Gai; Titiek Poerwati; Fitriah Maghfirah; Monsar Marito Sir (P4W LPPM IPB, 2020)
Sustainable livelihood is an activity that can help households in meeting their needs for survival. However, frequent flooding, increase in population growth each year, lack of facilities that support livelihoods such as education and health facilities, has made community’s livelihoods decline. Frequent flood results in reduced agricultural production. As a result, resources available at the research site become unbalanced. Therefore, this study aims to formulate a village development concept based on sustainable livelihood. This research was conducted in Surumana Village, Donggala Regency, Central Sulawesi Province by using primary and secondary data with a sample of 82 households. Likert scale was employed to measure one’s or group’s attitudes, opinions, and perceptions regarding social events or symptoms experienced. Besides, the Delphi method was also employed and used to gather opinions from experts through questionnaires with feedback mechanism while maintaining the anonymity of experts’ responses. The study result show that the maximum resource strength is found in social capital. Meanwhile, the vulnerability that affects resources in Surumana Village is flooding. In addition, the factors that support realization are institutions, education, health, transportation, reducing flooding, and increasing agricultural production.